Disputes between parents and children in the family and their impact on the upbringing - Xashimjanovna, Narzikulova Dilnoza (International Journal of Psychosocial Rehabilitation, 2020)
In this article the problem of conflicts between parents in family and their influence on the discipline will be revealed. Child up-bringing is the most important issues. We can be witness how the positive and negative relationship between parents affects to the child discipline. This article includes what we should pay attention to in bringing the child up and how we can make them ideal and perfect people.